Islam, Muslim and anthropology - Al-Qurtuby, Sumanto (Penerbit Universiti Kebangsaan Malaysia, 2021)
Is there a link between Islam and anthropology? Is there a need for anthropological study of Islam and its adherents (Muslim societies)? This article discusses the connection between Islam and anthropology as well as the vitality of anthropology as a significant component of the study of Islam and Muslim societies across the world. Moreover, it tries to examine Muslim society–related issues and themes anthropology should focus on in order to grasp the plurality and complexity of Islam and Muslim societies.